Pull-out of Upper Thoracic Pedicle Screws Can Cause Spinal Canal Encroachment in Growing Rod Treatment. Issue 7 (August 2018) - Bekmez, Senol; Kocyigit, Aykut; Olgun, Zeynep Deniz; Ayvaz, Mehmet; Demirkiran, Halil Gokhan; Karaagaoglu, Ergun; Yazici, Muharrem
Abstract : Background: Proximal foundation failure is a common complication of growing rod (GR) treatment for early-onset scoliosis. Spinal canal encroachment due to pull-out of pedicle screw used as proximal foundation has been anecdotally reported in GR patients. The aim of this study is to report the prevalence of spinal canal encroachment of pedicle screws in GR treatment and determine risk factors using a single-center cohort. Methods: Inclusion criteria were: (1) GR for early-onset scoliosis and (2) pull-out of at least 1 proximal anchor pedicle screw. Patients were divided into 2 groups according to the presence of medial screw migration. Medial migration of the screw was confirmed by computed tomography. The extracted data included demographic, clinical, and radiographic information. Results: A total of 21 patients (of 96) met inclusion criteria (21.8%). None of the screws appeared malpositioned on early postoperative x-ray. Average follow-up until screw failure was 50.4 months (64 to 85 mo) and average number of lengthenings 8.1 (4 to 13). Computed tomography revealed canal encroachment in 11 patients (group 1), and no encroachment in 10 (group 2). There was no significant difference between groups for age, follow-up or number of lengthenings. At the time of screw pull-out, coronal plane deformity was increased compared with early postoperative x-ray in all; however, this increase was significantly higher in group 1 (45.7 vs. 35 degrees, P =0.002). Proximal junctional angle (PJA) was increased in both groups at the time of pull-out. While not statistically significant, PJA increased linearly in group 1 but spiked in group 2 at the time of pull-out. There was no neurological event preoperatively, intraoperatively or postoperatively. Failed screws were safely revised in either planned/unplanned surgeries. Conclusions: In patients with proximal anchor failure of GR, especially if there is increase of coronal deformity and/or PJA, possible spinal encroachment should be kept in mind. Level of Evidence: Level IV—retrospective case series.